The Effect of Environmental and Social Performance on Earnings Management in the Sri-Kehati Index - Novi Eka Nadias; Rida Perwita Sari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The rapid development of the business world encourages business actors to carry out various strategies, including earnings management, to present good financial reports. Earnings management is a strategy to show positive financial information that contradicts actual conditions. On this basis, companies carry out earnings management to achieve the company's profit target in the future. This study is focused on proving the effect of environmental and social performance on earnings management with the population used, namely SRI-KEHATI Index companies listed on the IDX in 2020-2023. This research is a quantitative study with a sampling method, namely purposive sampling, so that a sample of 11 companies with 4 years of observation is obtained. The data used in this study are secondary data obtained through financial reports and company sustainability reports. Data analysis in this study used Partial Least Squares (PLS). The results showed that environmental performance has a significant effect on earnings management. Meanwhile, social performance does not affect earnings management.